Antunes, R. (eds). (2020). Uberização, Trabalho Digital e Indústria 4.0. [Uberization, Digital Work and Industry 4.0]. 1. Ed. São Paulo: Boitempo. - Salvagni, Julice; da Silva, Victória Mendoça (Cuadernos de Trabajo Social, 2021)
Book review of Antunes, R. (eds). (2020). Uberização, Trabalho Digital e Indústria 4.0. [Uberization, Digital Work and Industry 4.0]. 1. Ed. São Paulo: Boitempo.